Epidemiology and precision of SARS‐CoV‐2 detection following lockdown and relaxation measures. Issue 4 (29th December 2020) - Leuzinger, Karoline; Gosert, Rainer; Søgaard, Kirstine K.; Naegele, Klaudia; Bielicki, Julia; Roloff, Tim; Bingisser, Roland; Nickel, Christian H.; Khanna, Nina; Sutter, Sarah Tschudin; Widmer, Andreas F.; Rentsch, Katharina; et al.
Abstract: Objectives: Detecting severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is key to the clinical and epidemiological assessment of CoVID‐19. We cross‐validated manual and automated high‐throughput testing for SARS‐CoV‐2‐RNA, evaluated SARS‐CoV‐2 loads in nasopharyngeal–oropharyngeal swabs (NOPS), lower respiratory fluids, and plasma, and analyzed detection rates after lockdown and relaxation measures. Methods: Basel‐S‐gene, Roche‐E‐gene, and Roche‐cobas®6800‐Target1 and Target2 were prospectively validated in 1344 NOPS submitted during the first pandemic peak (Week 13). Follow‐up cohort (FUP) 1, 2, and 3 comprised 10, 999, 10, 147, and 19, 389 NOPS submitted during a 10‐week period until Weeks 23, 33, and 43, respectively. Results: Concordant results were obtained in 1308 cases (97%), including 97 (9%) SARS‐CoV‐2‐positives showing high quantitative correlations (Spearman's r > .95; p < .001) for all assays and high precision by Bland–Altman analysis. Discordant samples ( N = 36, 3%) had significantly lower SARS‐CoV‐2 loads ( p < .001). Following lockdown, detection rates declined to <1% in FUP‐1, reducing single‐test positive predictive values from 99.3% to 85.1%. Following relaxation, rates flared up to 4% and 12% in FUP‐2 and ‐3, but infected patients were younger than during lockdown (34 vs. 52 years, p < .001). In 261 patients providing 936 NOPS, SARS‐CoV‐2 loads declined by three orders of magnitude within 10 days postdiagnosis ( p < .001). SARS‐CoV‐2 loads in NOPS correlated with those in time‐matched lower respiratory fluids or in plasma but remained detectable in some cases with negative follow‐up NOPS, respectively. Conclusion: Manual and automated assays significantly correlated qualitatively and quantitatively. Following a successful lockdown, declining positive predictive values require independent dual‐target confirmation for reliable assessment. Confirmatory and quantitative follow‐up testing should be obtained within <5 days and consider lower respiratory fluids in symptomatic patients with SARS‐CoV‐2‐negative NOPS. Highlights: SARS‐CoV‐2‐loads decline by 1000‐fold within 10 days post‐diagnosis. Low prevalence settings require concordant dual‐target detection of SARS‐CoV‐2‐RNA. SARS‐CoV‐2 confirmation and follow‐up testing be obtained in <5 days post‐diagnosis. In symptomatic patients with SARS‐CoV‐2‐negative swabs, lower respiratory tract sampling be considered.